The normative permissiveness of political partyism - Tom Lane; Luis Miller; Isabel Rodriguez (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2023)
Political identity has become the strongest social divide within Western societies. This paper employs experiments to measure discrimination along multiple dimensions of social identity, and replicates previous findings showing the strongest discrimination against out-groups occurs in the political domain. Moreover, we explore a possible explanation for this phenomenon based upon social norms. We measure the social appropriateness of discrimination along each identity dimension. The ranking of dimensions by discrimination against out-groups reflects the extent to which such behaviour is normatively permissible, with the weakest anti-discrimination norms on the political dimension. Results are qualitatively similar in two European countries. We argue that, while norms sanctioning discrimination on other dimensions have developed historically, no such process has taken place in relation to political affiliation, bringing political identity to the fore and helping polarisation to flourish.
Keywords: C71; C92; D03; 330; social norms; polarization; group identity; laboratory experiments; discrimination